Cardiometabolic state links neurovascular burden with brain structure and function: Evidence from EEG and MRI - Daniel Franco-O’Byrne; Ana M. Castro-Laguardia; Carolina Delgado; James M. Shine; David Huepe; Raul González-Gomez; Enzo Tagliazucchi; Cecilia Gonzalez-Campo; Agustín Ibañez; Vicente Medel (NeuroImage)
Aging affects brain structure and function alongside metabolic and vascular processes leading to energetic impairments. While local neurometabolic dysfunction in aging is well-documented, the influence of systemic cardiometabolic and vascular markers on brain structure and function remains less understood. We examine the link between cardiometabolic dysfunction (measured by an allostatic load index) and neurovascular burden (measured by white matter hyperintensities), and their associations with brain changes, including ventricular and hippocampal volume, as well as EEG activity, across the adult lifesplan. Analyzing data from 196 healthy individuals across ages (20–75 years), we found a significant positive correlation between allostatic load index and white-matter hyperintensities, irrespective of age. White matter hyperintensities are also positively linked with ventricular enlargement, but not hippocampal atrophy. The allostatic load index mediated the relationship between white-matter hyperintensities and ventricular volume. Regarding brain function, changes in the spectral aperiodic exponent but not periodic alpha power were linked to white matter hyperintensities and the allostatic load index. The allostatic load index also mediated the relationship between spectral aperiodic exponent and white matter hyperintensities. Thus, findings suggest that the cardiometabolic state, as measured by the allostatic load index, plays a crucial role in brain health in aging, particularly influencing ventricular enlargement and increased aperiodic activity.